LANSOPRAZOLE IN THE TREATMENT OF ACUTE PEPTIC ULCER DISEASE - Manan, Alamzeb (Journal of Ayub Medical College Abbottabad, 1995)
ABSTRACT This is an open study conducted by the gastroenterology department of Ayub Medical College, Abbottabad. The aim was to study the effect and tolerance of lansoprazole in peptic ulcer disease, in a dose of 30 mg node. A total of 15 patients completed the trial, (Oesophageal ulcers 4, Gastric ulcers 4, Duodenal ulcers 7). Assessment was made clinically and endoscopically. The healing rate at the end of 6 weeks was 100%. The drug was well tolerated with no side effects. Most of these patients had taken H2 receptor antagonists without benefit. In conclusion lansoprazole is an effective and safe drug in healing acute peptic ulcers and is well tolerated.